KAJIAN MACAM PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL PADI ( Oryza sativa L.): Pupuk Organik, Padi, Mentik Wangi - mustakim, doni; Ratna Nurhayati, Dewi; Siswadi, Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2024)
The research entitled Study of Types of Organic Fertilizer on the Growth and Yield of Rice (Oriza sativa L.), research on rice with the Mentik Wangi variety was carried out in the rice fields of Dukuh Macanan Village, Jogosetran Village, Jogosetran Village, Kali Kotes District, March to July 2023. This research The aim is to examine types of organic fertilizer compared to inorganic fertilizer on the growth and yield of rice (Oriza sativa L.). The experimental design used was a Randomized Complete Block Design (RAKL) with a single treatment factor which was repeated 4 times and 6 treatments. The types of fertilizer used are pearl NPK fertilizer, organic Ore POC, Local POC, Local POC without eggs and fermented milk, Organic Urea POC. The observation data was analyzed using analysis of variance (ANOVA) and continued with the Duncan test with a level of 5%. The parameters observed include; plant height, number of tillers in a cluster, number of productive tillers, number of grain in a cluster, weight of grain in a cluster, weight of dry milled grain per plot, weight of 1000 seeds. The research results showed that the use of inorganic fertilizer showed the best results on the growth parameters and yields of rice plants compared to other types of organic fertilizer, but organic Orea POC also showed good results compared to other organic fertilizers on the yield and growth of rice (Oriza sativa L.).